War horse - Morpurgo, Michael (New York : Greenwillow Books, 2011)
Joey the horse recalls his experiences growing up on an English farm, his struggle for survival as a cavalry horse during World War I, and his reunion with his beloved master.
Keywords: Horses -- Juvenile literature; World War, 1914-1918 -- Juvenile fiction